An Analysis of the Effect of Employee’s Additional Income (TPP) and Work Ability on the Performance of the Civil Servants (ASN) at Regional Secretary of Central Bengkulu Regency - Cici Handika Dewi S; Siti Hanila; Nirta Vera Yustanti (Penerbit Jurnal Indonesia, 2021)
The importance of performance for ASN in government agencies is to achieve the goals that have been set as a whole, especially carrying out activities that are to improve and improve the welfare of the people in general. ASN performance is influenced by many factors including incentives in the form of Employee’s Additional Income (TPP) and ASN work ability itself. Incentives in this case in the form of TPP are factors that encourage ASN to work constructively according to institutional rules and become a stimulus that encourages ASN to work optimally for the institution. The purpose of this study was to determine the effect of Employee’s Additional Income (TPP) on the performance of the civil servants (ASN) at the Regional Secretary of Central Bengkulu Regency, to determine the effect of work ability on the performance of the civil servants (ASN) at the Regional Secretary of Central Bengkulu Regency and to determine the effect of Employee’s Additional Income (TPP) and work ability affect the performance of the civil servants (ASN) at the Regional Secretary of Central Bengkulu Regency. This study used a quantitative descriptive method where the sampling technique used was total sampling. So the number of samples in this study was 102 samples. In proving and analyzing data; validity, reliability, classical assumption test, multiple linear regression test and f test and t test were used. The test results show that 1) Employee’s Additional Income (TPP) and work ability together have an effect on employee’s performance. Regional Secretary of Central Bengkulu Regency with a significant value of 0.000. 2) Employee’s Additional Income (TPP) has a positive and significant effect on employee performance at the Regional Secretary of Central Bengkulu Regency, because the significant value is 0.000. 3) Work ability has a positive and significant effect on employee performance at the Regional Secretary of Central Bengkulu Regency, with a significant value of 0.001. Meanwhile, the percentage contribution of the influence of Employee’s Additional Income (TPP) and work ability on employee performance at the Regional Secretary of Central Bengkulu Regency was of 40.9%.